Toxina botulínica em crianças portadoras de paralisia cerebral tipo espástica - MACHADO FILHO, Dilvan Peres (2022)
Small alterations in the central nervous system can cause a serie of characteristic clinical events, depending on the area or cerebral region injured which can disclose at any time of the modified human life, since the formation until the complete development of the nervous system. When it occurs during the formation process or at birth, it can lead to a known pathology as not progressive chronic encephalopathy. also called Cerebral Paralysis. which manifests with characteristic clinical symptoms as dystonic syndromes, with or without extrapyramidals movements, ataxic syndromes, spasticity, difficulty in the march and the position harming the motor development of these children. During these years, literature has shown innumerable works describing a efficient treatment to reduce the sequels caused for this type of cerebral injury and, between several medications, it is distinguished the action of botulinic toxin, a powerful inhibitor of transmission of nervous impulse in the mioneural junction, reducing the hypertony in the infantile encephalopathy, minimizing the clinical signals and improving the position, balance, marches, muscular tonus and the quality of life of these children.The work was carried through in the Neurological Clinic of the “Hospital das Clinics Gaspar Vianna”, where it had the regular accompaniment in a group of 11 children, with age between 03 and 09 years, affected by spastic cerebral paralysis, “virgin type” of pharmacological or surgical treatment, submitted to the treatment with the botulinic toxin and followed, later evaluated in the act of the application, 7 and 30 days after first application, where the degree of spasticity, through the scale of Ashworth´S modified was identified, and the amplitude of the movement to articulate, through the goniometry in each one of the specific moments analysed bt T-test (Student) for analysis of the significance and comparison between the means, at the studied moments. In an evaluation with 90 days it was questioned to one of child familiars what they had found that changed after the treatment to verify effectiveness or success of the treatment.It was observed that there was a reduction in muscular tonus in all the patients. In the answers of the familiar ones, there was improvement in the quality of life of the children and the families, detected in the categories created from the speeches of the mothers, which had been: improving in playing, pain, more relaxed, calmer, reduction of crying, improving the position and execution of the voluntary movements. Hope was the answer that showed not only the effectiveness of the treatment, as the improvement in the quality of life, for the family and the patient.